Poison, lies, war: A mixed methods content analysis of posts about COVID-19 vaccination on Gab Social - Alice Marianne Fritz; Andrea M. Smith (Human Vaccines & Immunotherapeutics)
Recent surges in COVID-19 cases demonstrate the unabated transmissibility of this disease. Despite the ongoing threat of contagion, however, uptake of the COVID-19 vaccines, especially as booster doses, remains suboptimal among eligible adults and children in the United States, as reported by the World Health Organization (WHO). Public attitudes toward these vaccines remain balkanized, with some groups harboring ambivalence or even opposition to receiving inoculation. Given the challenges for public health posed by the current, and potentially, future pandemics, it is crucial to understand more about how laypersons discuss and frame the vaccination debate in informal, non- or minimally monitored spaces. Following their development, virtual groups were created to share stories about negative reactions to COVID-19 vaccines. Using a mixed methods approach, the present study analyzed a census of 368 posts on Gab Social that articulate users’ attitudes toward COVID-19 vaccination. Our approach focused on the framing and themes reflected in the posts, along with specific concerns expressed by users. Key findings include the observation that Gab users frequently frame the COVID-19 vaccination decision as one of whether the vaccines do more harm than good (i.e. helping vs. hurting frame) and that adverse reactions to the COVID-19 vaccines are not being truthfully reported on by mainstream media. Moreover, posts often display an antagonistic “Us vs. Them” perspective that pits vaccine skeptics against adherents. Overall, Gab users expressed strong resistance to the vaccines and distrusted government-issued recommendations to vaccinate, yet valorized medical professionals who advocated for more research on the vaccines’ safety. Through these investigations, we hope to derive insights that may inform COVID-19 vaccine promotion; accordingly, practical recommendations are suggested based on our findings.